(untitled) (Journal of Educational Management, 2016)
This paper is a review of the article making valid arguments in research ’Social difference and the politics of reports, and for reporting on small schooling in Africa: A Ghanaian case study’ by George J. Sefa Dei (2005). It reflects on the methodological orientation and how it affects the theoretical and substantive issues underpinning the study. The author Multicultural education particularly in makes a valid argument about the Euro-American contexts has configurations of power in knowledge received much attention in the production in higher education, as it relates to gender, ethnicity and religion. Nevertheless, the processes and its attendant challenges ’economical’ description of some aspects of the methodology, and limited use of data from underrepresented participants of cultural groups, usually as a result of higher education appear to defeat the immigration are often described as purpose of the investigation, multicultural. Multiculturalism Consequently, the projected voices in emphasizes the unique characteristics of the study seem to perpetuate the very of different cultures, especially as they phenomenon under criticism. Although the standards this paper applies to the review are most appropriate for doctoral writing, the issues raised have implications for This paper is a review of the article making valid arguments in research ’Social difference and the politics of reports, and for reporting on small aspect of large-scale studies